Rhetoric in British Politics and Society - Atkins, Judi.; Finlayson, Alan.; Martin, James; Turnbull, Nick.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Although the art of rhetoric is central to the practice of politics it also plays an important role in civic and private life. Using Aristotelian notions of ethos, pathos and logos, this collection offers engaging discussions on everything from Prime Minister's Questions and Welsh devolution to political satire and the rhetoric of cultural racism.
Keywords: Political science; Political theory; Democracy; Elections; Great Britain -- Politics and government; Political philosophy; Political Science and International Relations; British Politics; Political Theory; Political Philosophy; Political Science; Democracy; Electoral Politics